Inhibition of the STAT3 Signaling Pathway Contributes to the Anti-Melanoma Activities of Shikonin - Cao, Hui-Hui; Liu, Dong-Yi; Lai, Ye-Cai; Chen, Yu-Yao; Yu, Lin-Zhong; Shao, Meng; Liu, Jun-Shan (Frontiers in Pharmacology, 2020)
Background: Malignant melanoma is an extremely aggressive and metastatic cancer, and highly resistant to conventional therapies. Signal transducer and activator of transcription 3 (STAT3) signaling promotes melanoma development and progression, which has been validated as an effective target in melanoma treatment. Natural naphthoquinone shikonin is reported to exert anti-melanoma effects. However, the underlying mechanisms have not been fully elucidated. Purpose: This study aims to evaluate the anti-melanoma activities of shikonin and explore the involvement of STAT3 signaling in these effects. Methods: Zebrafish tumor model was established to evaluate the anti-human melanoma effects of shikonin in vivo. MTT assay and colony formation assay were employed to investigate the anti-proliferative effects of shikonin on human melanoma A375 and A2058 cells. Flow cytometry was used to analyze cell cycle distribution and apoptosis induction. Wound healing assay and Transwell chamber assay were conducted to examine the cell migratory and invasive abilities. Immunofluorescence assay was used to observe F-actin, Tubulin, and STAT3 localization. Western blotting was used to determine the expression levels of proteins associated with apoptosis and key proteins in the STAT3 signaling pathway. Immunoblotting was performed in DSS cross-linked cells to determine the homo-dimerization of STAT3. Gelatin zymography was employed to evaluate the enzymatic activity of MMP-2 and MMP-9. Transient transfection was used to overexpress STAT3 in cell models. Results: Shikonin suppressed melanoma growth in cultured cells and in zebrafish xenograft models. Shikonin induced melanoma cells apoptosis, inhibited cell migration and invasion. Mechanistic study indicated that shikonin inhibited the phosphorylation and homo-dimerization of STAT3, thus reduced its nuclear localization. Further study showed that shikonin decreased the levels of STAT3-targeted genes Mcl-1, Bcl-2, MMP-2, vimentin and Twist, which are involved in melanoma survival, migration and invasion. More importantly, overexpression of constitutively active STAT3 partially abolished the anti-proliferative, anti-migratory and anti-invasive effects of shikonin. Conclusion: The anti-melanoma activity of shikonin is at least partially attributed to the inhibition on STAT3 signaling. These findings provide new insights into the anti-melanoma molecular mechanisms of shikonin, suggesting its potential in melanoma treatment.